Estudio psicométrico del Rational Experiential Inventory en una muestra de estudiantes argentinos - Reyna, Cecilia (2016)
The Rational Experiential Inventory consist of two large scales (rational and experiential), each one with two subscales (ability and engagement). Their psychometric properties have been studied in several countries, but there are no reports in the Latin American context. In this study we analyzed the factor structure and internal consistency of the Rational Experiential Inventory, and assessed the relationships between processing styles and different personality dimensions in a sample of students from Argentina. The results show an underlying two-factor structure with good internal consistency values. Only one significant relationship between experiential style and extraversion was observed. A version with fewer items was attained and, due to its adequate psychometric properties, this instrument may be used in future research studies.